Emergence of Multidrug-Resistant Escherichia coli Producing CTX-M, MCR-1, and FosA in Retail Food From Egypt - Ramadan, Hazem; Soliman, Ahmed M.; Hiott, Lari M.; Elbediwi, Mohammed; Woodley, Tiffanie A.; Chattaway, Marie A.; Jenkins, Claire; Frye, Jonathan G.; Jackson, Charlene R. (Frontiers in Cellular and Infection Microbiology, 2021)
In this study, multidrug resistant (MDR) Escherichia coli isolates from retail food and humans assigned into similar Multilocus Sequence Types (MLST), were analyzed using whole genome sequencing (WGS). In silico analysis of assembled sequences revealed the existence of multiple resistance genes among the examined E. coli isolates. Of the six CTX-M-producing isolates from retail food, blaCTX-M-14 was the prevalent variant identified (83.3%, 5/6). Two plasmid-mediated fosfomycin resistance genes, fosA3, and fosA4, were detected from retail food isolates (one each from chicken and beef), where fosA4 was identified in the chicken isolate 82CH that also carried the colistin resistance gene mcr-1. The blaCTX-M-14 and fosA genes in retail food isolates were located adjacent to insertion sequences ISEcp1 and IS26, respectively. Sequence analysis of the reconstructed mcr-1 plasmid (p82CH) showed 96-97% identity to mcr-1-carrying IncI2 plasmids previously identified in human and food E. coli isolates from Egypt. Hierarchical clustering of core genome MLST (HierCC) revealed clustering of chicken isolate 82CH, co-harboring mcr-1 and fosA4 genes, with a chicken E. coli isolate from China at the HC200 level (≤200 core genome allelic differences). As E. coli co-harboring mcr-1 and fosA4 genes has only been recently reported, this study shows rapid spread of this genotype that shares similar genetic structures with regional and international E. coli lineages originating from both humans and food animals. Adopting WGS-based surveillance system is warranted to facilitate monitoring the international spread of MDR pathogens.